Effect of Proton Pump Inhibitors on the Management of GERD in the Department of Gastroenterology HMC Peshawar - Imran Ullah, Naeem Jan, Sadia Anjum, Farooque Islam, Ayesha Gulalai Marwat, Itizaz Hayat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In this trial, patients treated at the Department of Gastroenterology, Hayatabad Medical Complex in Peshawar, would have their gastroesophageal reflux disease (GERD) managed with proton pump inhibitor (PPI) medication. The treatment of omeprazole (40 mg once daily) or famotidine (40 mg O.D. daily) for 12 months was randomly allocated to 100 patients with GERD. The primary outcome measure was the mean change in oesophageal acid exposure time from baseline to twelve months. The frequency of GERD-related symptoms and general health-related quality of life over time were considered secondary objectives. Endoscopic results were also documented at the beginning and after a year. The study’s adverse occurrences were kept under observation. The findings demonstrated that from baseline to twelve months, the mean oesophageal acid exposure duration significantly decreased in both PPI groups (mean S.E., 18.9 1.7 minutes for omeprazole group against 16.4 2.1 minutes for famotidine group, p0.001). Additionally, the treatment groups substantially outperformed the control groups at twelve months compared to baseline regarding the mean Frequency of GERD-related symptoms and overall health-related quality of life (p 0.001). There were no documented severe adverse events. GERD may be effectively and safely treated with PPI medication, and there are no clinically significant differences between omeprazole and famotidine. Objectives: 1 To determine if proton pump inhibitors (PPIs) are safe and effective for treating GERD. 2 To contrast omeprazole and famotidine’s effectiveness and safety in treating GERD. 3 To compare the two therapy groups’ mean changes in oesophageal acid exposure duration from baseline to 12 months. 4 To compare the mean Frequency of GERD-related symptoms and overall health-related quality of life over time in the two therapy groups. 5 To determine if there are any adverse effects related to using PPIs for treating GERD. Methodology: Between January 2021 and January 2022, at the Department of Gastroenterology hmc Peshawar, the research was carried out over 12 months. One hundred GERD patients were recruited, and two groups were randomly allocated. The mean esophageal acid exposure duration significantly decreased in both PPI groups between baseline and 12 months (mean S.E., 18.9 1.7 minutes for the omeprazole group vs 16.4 2.1 minutes for the famotidine group, p0.001). There were no documented severe adverse events. Omeprazole (40 mg once daily) was administered to the first group, whereas famotidine (40 mg O.D. daily) was given to the second group over 12 months. Patients were assessed for factors such as esophageal acid exposure duration, frequency of GERD-related symptoms, general health-related quality of life, and endoscopic findings at baseline and each follow-up visit. Throughout the trial, adverse events were kept track it. Results: The findings demonstrated that both PPI groups significantly decreased their mean oesophageal acid exposure time from baseline to twelve months (the omeprazole group’s mean S.E. was 18.9 1.7 minutes compared to the famotidine group’s 16.4 2.1 minutes, p0.001). The treatment groups considerably outperformed the control groups at twelve months compared to baseline regarding the mean Frequency of GERD-related symptoms and overall health-related quality of life (p 0.001). No occurrences that caused great harm were reported. Conclusion: This research showed that PPI medication, with no clinically significant differences between omeprazole and famotidine, is an efficient and secure treatment for GERD. However, further research is required to assess PPIs’ long-term effectiveness and safety in treating GERD. Keywords: Gastroesophageal Reflux Disease, Proton Pump Inhibitors, Omeprazole, Famotidine, Efficacy, Safety